Analisis Penerapan Prosedur Audit Yang Disepakati Atas Kas dan Bank di Organisasi Untuk Meminimalkan Ketidakwajaran. - Putri Yasmin Nabibha; Wahyu Helmy Dimayanti Sukiswo (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2025)
This study aims to determine how the application of agreed procedures for financial information on cash and bank accounts in one organization. This organization is an association consisting of entrepreneurs engaged in international trade. This organization is based in DKI Jakarta and spreads its network to East Java. The request for agreed procedure services came from the internal management of the organization who felt there were indications of impropriety in cash recording. Over the past few periods, the organization's cash has been depreciating continuously, causing a significant deficit. This raises concerns regarding the possibility of irregular financial management that is not transparent and unaccountable. Therefore, the board requested assistance from Practicing Accountants to carry out agreed audit procedures on cash and bank accounts in the receipts and disbursements section. This study aims to provide a factual picture of the condition of cash and as a form of accountability of the management to members and other interested parties. Keywords: Agreed Audit Procedures, Cash and Banks, Organization